Acute hypoxaemic respiratory failure in immunocompromised patients: abandon bronchoscopy or make it better?. Issue 6 (12th December 2019) - Zinter, Matt S.; Cheng, Guang-Shing
Acute hypoxemic respiratory failure (AHRF) in immunocompromised patients is a challenging clinical problem associated with mortality rates of 40–60% in children and adults [1, 2]. Thus, we read with great interest the results of a pre-planned secondary analysis of a large multicentre observational cohort of 1611 immunocompromised adults with AHRF, as reported by Bauer et al. [3]. The authors described the diagnostic yield and outcomes of fibreoptic bronchoscopy (FOB) in this group of vulnerable patients with the a priori hypothesis that "bronchoscopy, with limited complications, would reduce the number of unidentified causes of respiratory failure and be associated with reduced hospital mortality." After a rigorous analysis of a highly annotated dataset, the authors conclude that "bronchoscopy was associated with improved diagnosis and changes in management but also increased hospital mortality." A discussion of the strengths and limitations of recent data associating bronchoscopy with mortality in immunocompromised adults with acute hypoxaemic respiratory failure http://bit.ly/31mMpGL